A 3D GIS tool for the detection of noise hot-spots from major roads. (July 2020) - Puyana-Romero, Virginia; Cueto, Jose Luis; Gey, Ricardo
Highlights: A new 3D GIS tool to identify and manage noise hot-spots is presented and tested. It selects the road stretches that contribute to the noise problems at the receivers. The outcomes generated enriches the scenario used to design the action plans. The information is presented in an understandable way for the decision-makers. Abstract: The proper identification and prioritization of noise hot-spots caused by roads require a spatial analysis that goes beyond the information provided by strategic noise maps. With this purpose, this paper describes the development and testing of a new 3D tool built using ArcGIS scripts, which has been created for this task. This tool provides "enhanced information" that can enrich the scenarios used in the decision-making process that accompanies noise action plans. The new tool was tested in a residential area crossed by the A-376 highway, in the province of Seville, Spain, since the use of real data can better show the capabilities of the new methodology. The tool was validated with a benchmark test using 20 stretches of the highway chosen at random among areas with the population exposed to more than 50 dB. The results show a relative mean error of 1.33% after analyzing 3597 receivers above 50 dB. This contributes to the credibility and confidence in the method. It was also proved that the new tool represents a substantial improvement in the detection of noise hot-spots compared to similar tools in 2D. Finally, one of the most important conclusions is that the new tool defines more precisely the extent of the road noise problem, determining exactly the contribution of each section of the road in each of the noise problems diagnosed by the road noise maps. Among other things, this makes it easy to quickly discard inefficient noise mitigation measures.